2020
DOI: 10.3390/molecules25235539
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Polyhydroxyalkanoates (PHAs) by the Valorization of Biomass and Synthetic Waste

Abstract: Synthetic pollutants are a looming threat to the entire ecosystem, including wildlife, the environment, and human health. Polyhydroxyalkanoates (PHAs) are natural biodegradable microbial polymers with a promising potential to replace synthetic plastics. This research is focused on devising a sustainable approach to produce PHAs by a new microbial strain using untreated synthetic plastics and lignocellulosic biomass. For experiments, 47 soil samples and 18 effluent samples were collected from various areas of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The results obtained are in accordance with previous studies stating the faster assimilation of carbon sources such as glucose and acetic acid compared to that of longer and branched volatile fatty acids [40]. Furthermore, it should be noted that the rate of carbon assimilation can highly depend on the environmental factors of temperature, pH and oxygen demand which directly affect bacterial activity [45][46][47]. For example, in this case Bacillus megaterium is a mesophilic bacterium, which grows in an optimal temperature of 30-37°C [48].…”
Section: Bacillus Sp Cultivation On Glucose -And Vfas-based Synthetic Mediumsupporting
confidence: 90%
“…The results obtained are in accordance with previous studies stating the faster assimilation of carbon sources such as glucose and acetic acid compared to that of longer and branched volatile fatty acids [40]. Furthermore, it should be noted that the rate of carbon assimilation can highly depend on the environmental factors of temperature, pH and oxygen demand which directly affect bacterial activity [45][46][47]. For example, in this case Bacillus megaterium is a mesophilic bacterium, which grows in an optimal temperature of 30-37°C [48].…”
Section: Bacillus Sp Cultivation On Glucose -And Vfas-based Synthetic Mediumsupporting
confidence: 90%
“…No PHA production occurred at 40 °C, while the strain was able to grow with a Cell Dry Weight of 3.41 and 2.51 g/L at 48 and 96 h, respectively, this indicates that the higher the Cell Dry Weight does not necessarily imply an increase in PHA production. Javaid et al [2020] demonstrated that the Stenotrophomonas maltophilia strain IAM 12423 showed poor decline in PHA yield at a temperature above 37 °C, while still recorded high amount of CDW.…”
Section: Effect Of Temperature and Initial Ph On The Pha Productionmentioning
confidence: 97%
“…Polyhydroxybutyrate (PHB) is produced from community wastewater with Enterobacter aerogens 12Bi strain (Ceyhan and Ozdemir 2011). Javaid et al (2020) reported PHA production from waste, such as wood chips, cardboard cutouts, plastic bottle cutouts, shredded polystyrene cups and plastic bags, using Stenotrophomonas maltophilia HA-16 with good yield. The bacterial isolates B2 (Enterobacter carcerogenus) could be considered as potential strain for the conversion of rice straw hydrolysate into PHA.…”
Section: Pha Production On Glucose and Rice Straw Hydrolysatementioning
confidence: 99%